KEBERADAAN TARI PIRIANG DIATEH KACO DI NAGARI BAYUR MANINJAU KECAMATAN TANJUNG RAYA KABUPATEN AGAM - Yuni Safitri; Afifah Asriati; Desfiarni Desfiarni (SENDRATASIK UNP, 2013)
Abstract This article aims to reveal and explain the existence of dance in Ateh Piriang Kaco in Nagari Bayur. Type of research is a qualitative, descriptive method. Object of study is the existence of dance in Ateh Piriang Kaco. Data obtained with a literature study, observation, interviews, photo shoots and documentation. Conducted data analysis with ethnographic techniques. The results showed that dance Piriang in Ateh Kaco still recognized to this day by people Bayur. This is evidenced by the still in use and functioning of dance Piriang in Ateh Kaco by the Cultural Bayur in social activities. Kata kunci: keberadaan, tari, Piriang, Ateh, Kaco